Design Considerations for Educational Mobile Apps for Young Children. (September 2017) - Mak, Derek; Nathan-Roberts, Dan
Mobile touchscreens are widely recognized as accessible educational tools to enhance the cognitive and intellectual development of children as young as two. Early-childhood educators readily integrate technology in the instruction of young children, preparing them to be digital citizens. This proceeding examines the body of research performed in child-computer interaction to inform designers on best practices for developing educational tablet applications. Young children may justifiably constitute a specialist user group, so special design considerations should be applied. These guidelines were formed by examining children's cognitive, physical, and emotional levels of development.